GPx3 knockdown inhibits the proliferation and DNA synthesis and enhances the early apoptosis of human spermatogonial stem cells via mediating CXCL10 and cyclin B1 - Wu, Si; Cheng, Zixin; Peng, Ye; Cao, Ying; He, Zuping (Frontiers in Cell and Developmental Biology, 2023)
Spermatogenesis is regulated by genetic and epigenetic factors. However, it remains largely unknown about the genes and signaling pathways mediating human spermatogenesis. Here we have for the first time explored the expression, function and mechanism of Glutathione peroxidase 3 (GPx3) in controlling the proliferation and apoptosis of human spermatogonial stem cells (SSCs). We found that GPx3 was expressed in human SSCs. Significantly, we revealed that GPx3 knockdown resulted in the decrease of proliferation, DNA synthesis and Cyclin B1 level of human SSC line, which possessed the phenotypic features of human primary SSCs. Flow cytometric analysis and TUNEL assays showed that GPx3 silencing led to the enhancement of early apoptosis of human SSC line. RNA-sequencing was utilized to identify CXCL10 as a target of GPx3 in human SSCs, and notably, both double immunostaining and Co-immunoprecipitation (Co-IP) demonstrated that there was an association between GPx3 and CXCL10 in these cells. CXCL10-shRNA resulted in the reduction of the proliferation and DNA synthesis of human SSC line and an increase of apoptosis of these cells. Taken together, these results implicate that GPx3 regulates the proliferation, DNA synthesis and early apoptosis of human SSC line via mediating CXCL10 and Cyclin B1. This study thus offers a novel insight into the molecular mechanism regulating the fate determinations of human SSCs and human spermatogenesis.